Exposure of low-concentration arsenic induces myotube atrophy by inhibiting an Akt signaling pathway. (June 2020) - Chiu, Chen-Yuan; Chung, Min-Ni; Lan, Kuo-Cheng; Yang, Rong-Sen; Liu, Shing-Hwa
Abstract: Arsenic, a widely distributed toxic metalloid, has been found to be associated with the low-birth-weight infants and the impairment of muscle regenerative capacity in areas with high levels of arsenic in drinking water. The distal muscular atrophy is one of side effects of arsenic trioxide (As2 O3 ) for acute promyelocytic leukemia therapy. We hypothesized that arsenic may be a potential risk factor for skeletal muscle atrophy. Here, we investigated the action and molecular mechanism of low-dose arsenic on the induction of skeletal muscle atrophy in a skeletal muscle cell model. The differentiated C2C12 myotubes were treated with As2 O3 (0.25–1 μM) for 48 h without apparent effects on cell viability. The signaling molecules for myotube atrophy were assessed. Submicromolar-concentration As2 O3 dose-dependently triggered C2C12 myotube atrophy and increased the protein expressions of atrogenes Atrogin1 and MuRF1 and inhibited the upstream phosphorylated proteins Akt and FoxO1, while As2 O3 dose-dependently increased AMPK phosphorylation in myotubes. Akt activator SC79 could significantly reverse the As2 O3 -induced myotube atrophy. These results suggest that arsenic is capable of inducing myotube atrophy by inhibiting an Akt signaling pathway. Highlights: Submicromolar-concentration As2 O3 dose-dependently triggered C2C12 myotube atrophy. As2 O3 induced protein expressions of atrogenes Atrogin1 and MuRF1. As2 O3 inhibited upstream phosphorylated proteins of atrogenes (Akt and FoxO1). Arsenic can induce myotube atrophy by inhibiting an Akt signaling pathway.